Recording surgical risk data in comprehensive dental care medical records - Maribel de las Mercedes Bastarrechea Milián; Agustín Rodríguez Soto; Denia Morales Navarro; Edelis Raimundo Padrón (Editorial Ciencias Médicas, 2022)
Introduction: Comprehensive dental care of surgical risk patients is a current challenge. Dental care professionals should have access to tools allowing them to expand their knowledge about possible surgical risks. Appropriately developed medical records are an example of such tools. Objective: To describe the process of development of medical records of surgical risk patients at Salvador Allende dental clinic. Methods: A total 108 medical records were reviewed, corresponding to all the surgical risk patients admitted to the general comprehensive dental care service of Salvador Allende dental clinic in the municipality of Cerro, Havana, in a three months' period. Results: Of the patients studied, 41.6% had arterial hypertension, followed by patients with two or more conditions (37.0%). It was found that 56.4% of the medical records contained information about the use of drugs for the underlying condition. The remaining items exhibited low percentages of data completion. 79.6% of the risk patients received surgical treatment. Conclusions: The most common risk condition is arterial hypertension, followed by patients with two or more diseases. The data required for the care of surgical risk patients are not recorded. The proposals put forth will make it possible to perform any professional practice in a more effective manner and with a lower level of risk.